Moribito : Guardian of the Spirit - Uehashi, Nahoko; Hirano, Cathy; Shimizu, Yuko, 1965- (New York : Arthur A. Levine Books, 2008)
The wandering warrior Balsa is hired to protect Prince Chagum from both a mysterious monster and the prince's father, the Mikado.
Translation of: Seirei no Moribito.
Booklist.
Horn Book.
School Library Journal.
Booklist, August 2008.
Bulletin (Center for Children's books), July 2008.
Keywords: Monsters -- Juvenile fiction; Princes -- Juvenile fiction; Fantasy; Monsters -- Fiction; Princes -- Fiction; Monsters -- Fiction; Princes -- Fiction; Fantastic fiction; Fantastic fiction